Reconstruction of Environmental Crime Prevention Policy Through a Green Policing Approach from the Perspective of Environmental Criminal Law Reform in Riau Province - I Made Juni Artawan; Ahmad Redi (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2026)
Environmental crimes, such as illegal logging, forest and land fires, and forest destruction remain serious problems in Indonesia, particularly in Riau Province, which has extensive forest and peatland areas and is vulnerable to various forms of environmental damage. Although various Environmental protection and management have been governed by laws and regulations, in practice, law enforcement against environmental crimes still faces various obstacles, both from regulatory, institutional, and effectiveness aspects of law enforcement. This study aims to analyze the legal regulations and implementation of the green policing concept in overcoming environmental crimes and formulate a reconstruction of policies for preventing environmental crime using a green policing approach from the standpoint of Riau Province's environmental criminal law reform. Normative juridical research with a legislative and analytical perspective is the research methodology used. The research results indicate that the application of the green policing concept has the potential to strengthen the environmental law enforcement system through a preventive, participatory, and collaborative approach with the community and other stakeholders. However, this concept has not been explicitly regulated in the national legal system, creating a normative vacuum in its implementation. Therefore, a reconstruction of environmental criminal law policy that integrates the green policing concept into the law enforcement system is needed to increase the effectiveness of environmental crime prevention sustainably, particularly in Riau Province